Analysis of the Effectiveness of Treatment Methods for Enamel Demineralization as a Complication of Orthodontic Treatment (Literature review) - Klitynska, О. В.; Kytastyi, О. І.; Sheveria, С. М.; Shetelya, В. В.; Odnoralov, А. І. (Actual Dentistry, 2026)
Orthodontic treatment is a common procedure, especially in children and adolescents. However, the duration of treatment may adversely affect oral health, including the development of caries and gingivitis. The purpose of the study is to analyze literary sources on the issues of complications of orthodontic treatment in the form of sources of enamel demineralization and the occurrence of caries. Materials and methods. The analytical-semantic method was used to collect and further systematize data on the prevalence of complications of orthodontic treatment, specifically sources of enamel demineralization and caries. Results. Orthodontic treatment with fixed appliances is a modern approach to correcting anomalies and deformities, but its duration can adversely affect the condition of the teeth’s enamel and dentin. A literature review demonstrates the effectiveness of combined methods for treating white spots, with the obligatory use of fluoride toothpaste. The most effective method for long-term results is infiltration with a composite material. Laboratory studies have demonstrated the positive effect of infiltration with composite materials, combined with caseinphosphopeptide-amorphous calcium phosphate and fluoride or with bioactive glass, on the stability of enamel demineralization treatment for white spots. Regular use of fluoride preparations and casein phosphopeptide will help achieve the desired outcomes of orthodontic therapy and healthy tooth enamel. Conclusions. During and after treatment, special attention should be paid to the quality of each patient’s oral hygiene, with patient-oriented selection of methods and hygiene products tailored to each patient. In the event of enamel demineralization, characterized by white spots, effective remineralization techniques should be used in an age-appropriate manner.